Questionnaire and Lactic Acid Sting Test Play Different Role on the Assessment of Sensitive Skin: A Cross-sectional Study - Pan Y; Ma X; Song Y; Zhao J; Yan S (Dove Medical Press, 2021)
Yao Pan,1- 3 Xue Ma,1,2 Yanqing Song,1,2 Jinfeng Zhao,1,2 Shiyu Yan1,2 1Department of Cosmetics, College of Chemistry and Materials Engineering, Beijing Technology and Business University, Beijing, 100048, People's Republic of China; 2Beijing Key Laboratory of Plant Research and Development, Beijing, 100048, People's Republic of China; 3Institute of Cosmetic Regulatory Science, Beijing Technology and Business University, Beijing, 100048, People's Republic of ChinaCorrespondence: Yao PanDepartment of Cosmetics, College of Chemistry and Materials Engineering, Beijing Technology and Business University, Beijing, People's Republic of ChinaTel +86-10-68984937Email panyao@btbu.edu.cnBackground: Questionnaires and lactic acid sting test (LAST) are two widely used methods to identify sensitive skin. However, the self-perceived sensitive skin by questionnaires was not consistent with the determination of LAST.Objective: The aim of the study was to measure the biophysical properties noninvasively of sensitive skin evaluated by questionnaire and LAST and to investigate their correlations with the scores of questionnaire and LAST.Methods: A total of 209 healthy Chinese females completed the study. Self-assessment questionnaire and LAST were both performed to identify sensitive skin. Epidermal biophysical properties, including skin hydration, transepidermal water loss (TEWL), sebum content, erythema index (EI), a* value, L* value, skin elasticity, and skin pH, were measured with noninvasive instruments.Results: The frequency of sensitive skin was 50.2% and 66.0% by questionnaire and LAST, respectively. Subjects with self-assessed sensitive skin had a slightly higher LAST positive rate. Skin hydration, sebum content, a* and EI values were significantly higher in the self-assessed sensitive skin group, while TEWL, a* and EI values increased but L* value decreased with significance in the LAST positive group. The LAST stingers among sensitive skin subjects had higher EI but not in the healthy skin subjects. In addition, questionnaire scores positively correlated with skin hydration, sebum content, a* and EI values, while a positive relationship of LAST scores with TEWL, a* and EI values was observed. The scores of questionnaire and LAST both negatively related to L* value.Conclusion: Self-assessed questionnaire is associated with sensitive skin featured by oily and red face without impaired barrier function, whereas LAST is suitable to identify fragile skin barrier and enhanced blood flow on the face. Combination of both methods to diagnose sensitive skin might be more reliable.Keywords: sensitive skin, questionnaire, lactic acid sting test, biophysical parameters